Educação sexual emancipatória: análise crítica da Base Nacional Comum Curricular e possíveis alternativas. - Castro, Rafael Borba de (Universidade Federal de São Carlos, 2021)
In view of the advance of neoliberalist policies resumed after the intensification caused by the political-media coup, Brazilian education is under attack by numerous attempts at precariousness and control by the capitalist market, so, this work will discuss the document that most represents the scenario currently, the National Curriculum Common Core, which is imposed by the government as a democratic curriculum, which will reduce inequalities in basic education levels. Then, this work is concerned with analyzing how traditional and technical teaching, present in the document, shows itself in the teaching of Science and Biology, and also, in denouncing the absence, delete and concealment of themes related to gender and sexuality in school content, which the BNCC aims to prescribe. Therefore, in addition to qualitative document analysis, an essential part of this work is summarized in proposing a project of lesson plans on Emancipatory Sexual Education, which differs from the traditional method of talking about the theme of sexuality, since it covers it from perspectives of humanization of the subjects involved in educational practices, not forgetting the fact that this dimension is historically constructed.
Emancipatory sex education: critical analysis of the Common Base Core and possible alternatives
Keywords: Educação Sexual Emancipatória; Base Nacional Comum Curricular; Temática; Emancipatory Sex Education; National Curriculum Common Base Core; Thematic Research; Paulo Freire; CIENCIAS HUMANAS::EDUCACAO::CURRICULO